1991
DOI: 10.1021/bi00220a002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic evidence for two nucleotide binding sites on the calcium ATPase of sarcoplasmic reticulum

Abstract: The CaATPase of sarcoplasmic reticulum was reacted with [gamma-32P]ATP to form the covalent phosphoenzyme intermediate. Noncompetitive inhibition by reactive red-120 and chelation of calcium allowed us to monitor single-turnover kinetics of the phosphoenzyme reacting with water or added ADP at 0 degrees C. When ADP was added and the amount of product, [gamma-32P]ATP, formed was measured, we found that added cold ATP did not interfere with the phosphoenzyme reacting with ADP. We conclude that ATP cannot bind wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…3, the modulatory effect on E 2 P hydrolysis should, therefore, be apparent only for the highest MgATP concentrations. A subject of much controversy is the question whether the phosphorylating and modulatory MgATP/ATP molecules are at the same locus, exhibiting variable affinity during the transport cycle depending on conformational state, or a separate low affinity allosteric site exists on the same Ca 2ϩ -ATPase polypeptide chain (14,29,(55)(56)(57)(58). A similar discussion exists for the closely related Na ϩ ,K ϩ -ATPase, although in this case it seems that only the E 2 (K 2 ) 3 E 1 (Na 3 ) transition and not phosphoenzyme processing is modulated by nucleotide (59 -62).…”
Section: Discussionmentioning
confidence: 99%
“…3, the modulatory effect on E 2 P hydrolysis should, therefore, be apparent only for the highest MgATP concentrations. A subject of much controversy is the question whether the phosphorylating and modulatory MgATP/ATP molecules are at the same locus, exhibiting variable affinity during the transport cycle depending on conformational state, or a separate low affinity allosteric site exists on the same Ca 2ϩ -ATPase polypeptide chain (14,29,(55)(56)(57)(58). A similar discussion exists for the closely related Na ϩ ,K ϩ -ATPase, although in this case it seems that only the E 2 (K 2 ) 3 E 1 (Na 3 ) transition and not phosphoenzyme processing is modulated by nucleotide (59 -62).…”
Section: Discussionmentioning
confidence: 99%
“…ATP could change depending on the enzyme conformation (Reynolds et al, 1985). Two distinct sites have also been postulated, one catalytic and one regulatory (de Meis and de Mello, 1973;Coll andMurphy, 1985,1991). However, it has been recently demonstrated that only 1 mol ATP binds/mol Ca2+-ATPase under various conditions (Champeil et al, 1988;Oliveira et al, 1988;Lacapere et al, 1990a) and the most probable explanation for the activation is that a second ATP could bind following phosphorylation and ADP dissociation (Cable et al, 1985;Champeil and Guillain, 1986;Bishop et al, 1987;Lacapere, 1987;Champeil et al, 1988).…”
Section: The Reaction Mechanism Ofmentioning
confidence: 99%
“…ATP could change depending on the enzyme conformation (Reynolds et al, 1985). Two distinct sites have also been postulated, one catalytic and one regulatory (de Meis and de Mello, 1973;Coll and Murphy, 1985,1991 Abbreviations. SR, sarcoplasmic reticulum; kobsr observed rate constant; k,,, association rate constant; koff, dissociation rate constant; Kp, equilibrium constant of phosphorylation; Vo, initial rate; Np,ATP, 2'(3')-0-(2,4,6-trinitrophenyl)adenosine 5'-triphosphate.…”
mentioning
confidence: 99%
“…On the other hand, the B tryptic segment folds over to allow proximity of Gly626 and Asp627 (70) and Cys670 and Cys674 (81) to the phosphorylation site. This proximity is substantiated further by crosslinking of A1 and B tryptic fragments following formation of a carbodiimide-ATP adduct at the phosphorylation site (84).…”
Section: Spatial Relationships Of Catalytic Site and Spectroscopicmentioning
confidence: 81%